2016
DOI: 10.1097/md.0000000000005546
|View full text |Cite|
|
Sign up to set email alerts
|

Nuclear expression and/or reduced membranous expression of β-catenin correlate with poor prognosis in colorectal carcinoma

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 58 publications
(55 reference statements)
1
9
0
1
Order By: Relevance
“…Prior work in SBA has noted abnormal nuclear accumulation of b-catenin as a marker of WNT activation in 20% to 41% of cases, and in one study correlated with worse overall survival (26,27). In colorectal cancer, despite near universal alterations in the APC gene, abnormal b-catenin expression is observed in a limited number of cases, often heterogenous within a tumor, and of unclear prognostic significance (28,29). Thus, as in colorectal cancer, additional factors besides single alterations in the WNT pathway genes are likely involved with downstream WNT-related protein expression.…”
Section: Discussionmentioning
confidence: 99%
“…Prior work in SBA has noted abnormal nuclear accumulation of b-catenin as a marker of WNT activation in 20% to 41% of cases, and in one study correlated with worse overall survival (26,27). In colorectal cancer, despite near universal alterations in the APC gene, abnormal b-catenin expression is observed in a limited number of cases, often heterogenous within a tumor, and of unclear prognostic significance (28,29). Thus, as in colorectal cancer, additional factors besides single alterations in the WNT pathway genes are likely involved with downstream WNT-related protein expression.…”
Section: Discussionmentioning
confidence: 99%
“…Membranous expression of β-catenin exerts a restrictive effect on tumor cell movement and growth. Loss of β-catenin expression on the cell surface is an EMT associated event and increases cell motility, growth, and transformation and thus promote tumorigenesis [ 36 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, in studies to localize AJ proteins in colorectal tumors, membrane-bound ␤-catenin was intensely reduced, although it was difficult to discern whether or not there was an increase in ␤-catenin in the nucleus because of the different tumor stages that were detected and excessive disruption of tissue architecture through-out these tissues. Nonetheless, several studies have also shown that loss of membrane-bound E-cadherin and ␤-catenin is closely associated with a poorer prognosis in colorectal cancer patients (1,5,37). In addition, we have evidence that the absence of ClC-2 along with disruption of AJs promote colitisassociated tumorigenicity through increased activation of TCF/ LEF1 target genes.…”
Section: Discussionmentioning
confidence: 54%